Productivity and economics of clusterbean (Cyamopsis tetragonoloba) as influenced by phosphorus fertilization and biofertilizers in western Rajasthan - Choudhary, Ram Singh; Yadav, R.S.; Amin, Abdul (Annals of Agricultural Research, 2014)
Short communication